Rural Geography in Russia, Ukraine and in Belarus - a literature review - Karácsonyi, Dávid (Hungarian Geographical Bulletin, 2011)
The article is an overview of the literature on rural geography published in the Commonwealth of Independent States during the two decades that passed since the breakup of the Soviet Union. First, a brief review of the Soviet period is presented. A description of the current methodological approach and of the main sources follows. Finally, the studies devoted to rural areas of Russia, Ukraine and Belarus are introduced. The sources of the analysis mainly include works in English, German, Russian and Ukrainian. The literature review covers rural geography of Russia, Ukraine, and Belarus, and in the case of Russia it is focused on its European section.